Design of transversely-graded foam and wall thickness structures for crashworthiness criteria. (1st May 2016) - Fang, Jianguang; Gao, Yunkai; An, Xiuzhe; Sun, Guangyong; Chen, Junning; Li, Qing
Abstract: Foam-filled thin-wall structures have exhibited considerable advantages in energy absorption with light weight and have been widely used as energy absorber in engineering. Unlike existing uniform or mono-gradient structures, this paper introduces a novel dual functionally graded structure with changing both foam density and wall thickness along the transverse direction, namely transverse functionally graded foam-filled and functionally graded wall thickness (FGF-FGT) structures. According to different combinations of gradient directions in foam density and wall thickness, four different patterns are considered here. Based on the established surrogate models, the surface plots of crashworthiness criteria indicate that the combination of gradient patterns and the gradient exponents have significant effect on overall crashing performances. The multiobjective particle swarm optimization (MOPSO) algorithm is then adopted to seek optimal gradients of wall thickness and foam density, aiming to simultaneously improve the specific energy absorption ( SEA ) and reduce the maximum force ( F max ). The optimization results indicate that the transverse FGF-FGT structures with ascending grading patterns in both FGF and FGT is superior to the uniform counterparts and other graded structures, providing the designer with the promising optima in a Pareto sense.